Rejecting options from large and small choice sets: the mediating role of confidence. (10th September 2018) - Chan, Eugene; Wang, Yitong
Abstract : Purpose: Literature on choice has predominantly focused on selection decisions rather than rejection decisions. Research on rejection decisions has also only studied rejecting one option from two alternatives. This research aims to study the differences in decision confidence and satisfaction in rejection decisions between choice sets of small and large sizes. Design/methodology/approach: The authors conducted three behavioral experiments in which they first tested the overall effect (Experiment 1) and then found out whether regulatory focus (Experiment 2) and the attractiveness of options (Experiment 3) moderated it. Findings: The authors observed that decision satisfaction increased when rejecting larger (vs smaller) choice sets. Decision confidence mediated it (Experiment 1). The effect was strongest when participants had a prevention focus (Experiment 2) and when they were rejecting relatively unattractive options (Experiment 3). Research limitations/implications: This research expands the understanding of how individuals make rejection-based decisions and in particular how individuals make choices for one option out of many as in the selection-based choice overload literature. Practical implications: The authors show how choice sets of varying sizes affect rejection decisions commonly faced by managers and consumers. This research provides implications for improving confidence and satisfaction, both of which are important elements of everyday decision-making, by suggesting that choice outcomes may differ depending on whether one is making a selection or a rejection decision and whether the choice set size is small or large. Originality/value: This is the first study to examine rejection decisions with more than two alternatives. The findings complement the large body of work on the choice overload effect that focuses on selection decisions.